The Equity Funding Papers (Book). - Burns, Thomas J.; Leathers, Park E. (The Accounting Review, 1978)
Reviews the book "The Equity Funding Papers: the Anatomy of a Fraud," by Lee J. Seidler, Frederick Andrews and Marc J. Epstein.